Estrutura, diversidade e discriminação de comunidades vegetais em inselbergs do Espírito Santo, Brasil - Pinto Junior, Herval Vieira (2017)
Inselbergs are isolated rock outcrops that arise abruptly above the surrounding plains and are characterized by edaphic conditions and extreme climatic conditions. These surroundings are home to a high vegetation diversity and endemism, stand out worldwide next to the rupicolous vegetation of Madagascar and Eastern Australia. This study aims to describe and analyze the main structure of rupicolous plant communities of the State of Espírito Santo and discriminate these communities through species associations with the microhabitat preference of some species for specific habitats and its indicator species. Four Inselbergs in Espírito Santo were selected for your sampling vegetation: Águia Branca (Northwest Region), Pedra do Elefante (Northern Region), Forno Grande and Pedra de Pontões (Southern Region). For the sampling of vegetation was used the method of Intersection Line. The floristic similarity between the fields of study was tested through a Cluster Analysis, using the Jaccard distance and UPGMA. The data of the structure of vegetation and a categorization of sampling units were used to carry out an Analysis of Multidimensional Scaling (NMDS) in order to discriminate these communities through species associations with the microhabitat, habitat preference and specific indicator species. The Index Indicator Value (IndVal) was used to verify the occurrence of indicator species of microhabitat. The four communities present floristic composition comparable to other studies on rocky outcrops, where families with greater wealth were Asteraceae, Bromeliaceae, Cyperaceae, Melastomataceae, Orchidaceae, Poaceae and Velloziaceae. The four communities presented oligarchic structure and Shannon Index between 0.89 and 2.65. The dendrogram showed high similarity dissimilarity between the communities studied and Cofenetic Correlation Coefficient = 0.96. The results of analysis of NMDS indicate discrimination against groups within each Inselberg influenced by the microtopography results and the abundance of the species. These groups indicate the presence of similar microhabitats, as Monocotyledonous Mats, Depressions and Epilithic Vascular Plants based on the type of microtopography results (convex, concave or flat), but with floristic composition, physiognomy and structure specific to each Inselberg. The structure divided into groups confirms the existence of an organization in the form of mosaic this mosaic is based on concave and convex microtopography results, where resource availability is variable. The presence of exotic species such as Melinis minutiflora indicates the need for the management and conservation of holdings to avoid losing the rest of existing biodiversity, especially in the conservation units that are part of this study.